KAJIAN SIFAT MEKANIK BETON RINGAN DENGAN PENGGUNAAN POLYSTYRENE SEBAGAI BAHAN SUBSTITUSI AGREGAT HALUS - Siamet Widodo (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2005)
ABSTRACTLightweight concrete offers some advantages in reinforced concreteconstruction. It can be produced by replacing the normal aggregate (sand andgravel) with lightweight aggregate, either partially or fully, depending upon therequirements of density and strength. The present study covers the use ofexpanded polystyrene as fine lightweight aggregate in order to produce structurallightweight aggregate.These mixes were designed by using several variances of polystyrenevolume percentage by total fine aggregate. The substitution was done with 0%,25%, 500/0, 750/0 and 1000/0 by total volume of fine aggregate, with 0,50 watercement ratio. The Properties of hardened concrete namely compressive strength,splitting tensile strength and flexural strength were tested in 28 days of curingperiod.It is observed that polystyrene lightweight concrete has sufficient strengthto be accepted as structural lightweight concrete in 25~'O substitution by totalvolume of fine aggregate, with 17,35 MPa of compressive strength, but thecompressive strength will always decrease depending on the increasing ofpolystyrene percentage. The splitting tensile strength of polystyrene lightweightaggregate approximately 14%--18% of its compressive strength,for the normalconcrete it is nearly 10% of 28 days compressive strength. The flexural strengthwas ranging between 20%-30% of its compressive strength, higher than normalconcrete that nearly 15% of its compressive strength.Keywords: lightweight concrete, mechanical properties, polystyrene